Criminal Prevention and Support for Children Against Sexual Violence by Pedophiles - Ahmadi Pournazari, Najmeh; Rajabi Tajamir, Ebrahim; Fakheri, Nariman (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aims to identify the common characteristics of pedophiles, preventive measures against sexual violence towards children, necessary support after incidents of sexual violence, and the underlying factors contributing to both becoming a pedophile and victimization by pedophiles. The research focuses on understanding these aspects to develop comprehensive strategies for prevention, intervention, and support. Methods and Materials: This qualitative research was conducted in Karaj, Iran, involving experts in psychiatry and law who specialize in sexual violence by pedophiles. A total of 10 participants, including 5 psychiatric experts and 5 legal experts, were selected through snowball sampling. Data were collected using semi-structured interviews until theoretical saturation was achieved. NVivo software was utilized for organizing and analyzing the qualitative data. The Delphi technique was employed in a multi-stage process to achieve consensus among experts on the identified sub-dimensions and operational indicators. Findings: The study identified several common characteristics among pedophiles, such as medical history, psychological issues, family problems, and criminal records. Preventive measures included enhancing knowledge and awareness, implementing control measures, defining family boundaries, and strengthening legal punishments. Necessary support for victims emphasized appropriate parental reactions, counseling, and empathy. Underlying factors contributing to pedophilia and victimization were categorized into economic, social, and cultural influences. The study also found that comprehensive educational programs targeting both children and parents and holistic support systems are crucial in addressing the issue. Conclusion: Addressing pedophilia and child sexual violence requires a multi-faceted approach that includes prevention, intervention, and support strategies. By understanding the characteristics of pedophiles, implementing effective preventive measures, and providing necessary support to victims, the impact of this crime can be mitigated. Strengthening family and community support systems and incorporating culturally sensitive approaches are essential in creating a safer environment for children.